Dye Stabilization and Wavelength Tunability in Lasing Fibers Based on DNA. Issue 22 (16th September 2020) - Persano, Luana; Szukalski, Adam; Gaio, Michele; Moffa, Maria; Salvadori, Giacomo; Sznitko, Lech; Camposeo, Andrea; Mysliwiec, Jaroslaw; Sapienza, Riccardo; Mennucci, Benedetta; Pisignano, Dario
Abstract: Lasers based on biological materials are attracting an increasing interest in view of their use in integrated and transient photonics. Deoxyribonucleic acid (DNA) as optical biopolymer in combination with highly emissive dyes has been reported to have excellent potential in this respect. However, achieving miniaturized lasing systems based on solid‐state DNA shaped in different geometries to confine and enhance emission is still a challenge, and the physicochemical mechanisms originating fluorescence enhancement are not fully understood. Herein, a class of wavelength‐tunable lasers based on DNA nanofibers is demonstrated, for which optical properties are highly controlled through the system morphology. A synergistic effect is highlighted at the basis of lasing action. Through a quantum chemical investigation, it is shown that the interaction of DNA with the encapsulated dye leads to hindered twisting and suppressed channels for the nonradiative decay. This is combined with effective waveguiding, optical gain, and tailored mode confinement to promote morphologically controlled lasing in DNA‐based nanofibers. The results establish design rules for the development of bright and tunable nanolasers and optical networks based on DNA nanostructures. Abstract : Miniaturized, wavelength‐tunable lasers based on deoxyribonucleic acid (DNA) nanofibers might combine enhanced stability of embedded dyes and tailored emission through morphology control. Here, these systems are studied by a quantum chemical investigation of the DNA–dye interactions, and elucidated in their waveguiding and mode confinement properties that lead to morphologically tailored lasing from the doped DNA structures.